What do cochrane systematic reviews say about interventions for enuresis in children and adolescents? An overview of systematic reviews. Issue 4 (August 2022) - Moretti, Eduarda; Barbosa, Leila; da Silva, Ivson Bezerra; de Lima, Anna Myrna Jaguaribe; Lemos, Andrea
Summary: Objective: To conduct an overview of Cochrane systematic reviews about treatment alternatives for children and/or adolescents with enuresis. Sources: An overview of Cochrane systematic reviews about interventions for enuresis in children/adolescents was developed between September/2021 and December/2021. The protocol was registered on PROSPERO and the search was conducted only in the Cochrane Library database without any restriction. Reviews involving any type of intervention for the treatment of enuresis in children/adolescents were included. The risk of bias was assessed using Risk of Bias in Systematic Reviews (ROBIS) and the quality of reviews was assessed using A Measurement Tool to Assess Systematic Reviews (AMSTAR-2). Summary of the findings: Seven systematic reviews were identified. Based on the ROBIS assessment, all reviews were classified as low risk of bias. According to the AMSTAR-2 assessment, the three oldest systematic reviews were rated as critically low quality, one review was moderate quality, and the three most recent systematic reviews were rated as high quality. No difference was shown between alarm and desmopressin for a complete response to therapy after treatment (RR = 1.30; 95%CI: 0.92 to 1.84), but alarm use is related to a lower risk of adverse events (RR = 0.38; 95%CI: 0.20 to 0.71). There is a moderate certainty that the association between imipramine and oxybutynin is better than placebo to reduce the risk of children who do not achieve 14 consecutive dry nights after treatment (RR = 0.43; 95%CI: 0.23 to 0.78). Conclusions: There is no difference between alarm and desmopressin for enuresis treatment. However, alarm therapy had fewer adverse events than desmopressin. Moreover, combination therapy between imipramine and oxybutynin is better than placebo.